1973
DOI: 10.1172/jci107173
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cyclic Adenosine Monophosphate Metabolism in Human Bronchial Asthma. I. LEUKOCYTE RESPONSIVENESS TO β-ADRENERGIC AGENTS

Abstract: A B S T R A C T In an effort to better define the role of P-adrenergic blockade in human bronchial asthma, peripheral blood leukocytes and lymphocytes from individuals with this condition were studied for possible alterations in cyclic AMP metabolism. Using a previously described radioimmunoassay to measure cyclic AMP, cells from asthmatic subjects were shown to have a highly significant decrease in their cyclic AMP response to 8-adrenergic agents (isoproterenol, norepinephrine, and epinephrine) by comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1

Year Published

1974
1974
1986
1986

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(82 citation statements)
references
References 20 publications
3
78
1
Order By: Relevance
“…From Table III (Illiano et al, 1973;Parker & Smith, 1973;Bourne et al, 1973;Parker et al, 1974;Sandler et al, 1975;Goldberg & Haddox, 1977;Atkinson et al, 1977;Polgar et al, 1977;Takemoto et al, 1978). However, only a few data have been reported on cyclic nucleotide patterns in purified preparations of human T and B lymphocytes.…”
Section: Methodsmentioning
confidence: 99%
“…From Table III (Illiano et al, 1973;Parker & Smith, 1973;Bourne et al, 1973;Parker et al, 1974;Sandler et al, 1975;Goldberg & Haddox, 1977;Atkinson et al, 1977;Polgar et al, 1977;Takemoto et al, 1978). However, only a few data have been reported on cyclic nucleotide patterns in purified preparations of human T and B lymphocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, in vitro studies using leukocytes from non-atopic and from asthmatic subjects have been used extensively to monitor 3-adrenoceptor function and 13-adrenoceptor density (Parker & Smith, 1973;Kariman & Lefkowitz, 1977;Galant et al, 1978a,b;Brooks et al, 1979;Morris, 1980). However, controversy remains as to whether the reduced 3-adrenoceptor responsiveness and the reduced 3-adrenoceptor density observed in lymphocytes harvested from asthma sufferers, were directly related to therapy with 3-adrenoceptor agonists (Galant et al, 1978a,b; Morris, 1980) and/or to the disease state (Parker & Smith, 1973;Brooks et al, 1979). Furthermore, studies in lymphocytes may not always reflect the status of 3-adrenoceptors in the lung (Harvey & Tattersfield, 1982;Tashkin et al, 1982;Hasegawa & Townley, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It was also hypothesized that decreased beta-adrenergic response in asthma was not limited to the airways but a generalized phenomenon. Both in vivo and in vitro studies with isolated tissues have found decreased beta-adrenergic response in asthma (8)(9)(10)(11)(12). However, an altered response to histamine in isolated tissue has not yet been described in asthma (13).…”
Section: Introductionmentioning
confidence: 99%